4‐Deoxyraputindole C induces cell death and cell cycle arrest in tumor cell lines. Issue 6 (7th December 2018) - Vital, Wagner D.; Torquato, Heron F. V.; Jesus, Larissa de Oliveira Passos; Judice, Wagner Alves de Souza; Silva, Maria Fátima das G. F. da; Rodrigues, Tiago; Justo, Giselle Zenker; Veiga, Thiago A. M.; Paredes‐Gamero, Edgar J.
Abstract: Several molecules extracted from natural products exhibit different biological activities, such as ion channel modulation, activation of signaling pathways, and anti‐inflammatory or antitumor activity. In this study, we tested the antitumor ability of natural compounds extracted from the Raputia praetermissa plant. Among the compounds tested, an alkaloid, here called compound S4 (4‐Deoxyraputindole C), showed antitumor effects against human tumor lineages. Compound S4 was the most active against Raji, a lymphoma lineage, promoting cell death with characteristics that including membrane permeabilization, dissipation of the mitochondrial potential, increased superoxide production, and lysosomal membrane permeabilization. The use of cell death inhibitors such as Z‐VAD‐FMK (caspase inhibitor), necrostatin‐1 (receptor‐interacting serine/threonine‐protein kinase 1 inhibitor), E‐64 (cysteine peptidases inhibitor), and N ‐acetyl‐ L ‐cysteine (antioxidant) did not decrease compound S4‐dependent cell death. Additionally, we tested the effect of cellular activity on adherent human tumor cells. The highest reduction of cellular activity was observed in A549 cells, a lung carcinoma lineage. In this lineage, the effect on the reduction of the cellular activity was due to cell cycle arrest, without plasma membrane permeabilization, loss of the mitochondrial potential or lysosomal membrane permeabilization. Compound S4 was able to inhibit cathepsin B and L by a nonlinear competitive (negative co‐operativity) and simple‐linear competitive inhibitions, respectively. The potency of inhibition was higher against cathepsin L. Compound S4 promoted cell cycle arrest at G 0 and G 2 phase, and increase the expression of p16 and p21 proteins. In conclusion, compound S4 is an interesting molecule against cancer, promoting cell death in the human lymphoma lineage Raji and cell cycle arrest in the human lung carcinoma lineage A549. Abstract : The alkaloid 4‐Deoxyraputindole C was isolated from Raputia praetermissa plant 4‐Deoxyraputindole C–induced cell death by necrosis in a lymphoma lineage 4‐Deoxyraputindole C did not induce cell death in a lung carcinoma lineage, but cell cycle arrest.